Iteration Analysis of Reading Materials in ELT Book, Developing English Competencies 3: (Analisis Pengulangan Kata Materi Ajar Membaca dalam Buku Ajar Bahasa Inggris, Developing English Competencies 3) - Ro’ifah (LPPM Universitas PGRI Adi Buana, 2019)
Learning a language is fundamental and deeply dependent on vocabulary. To be selective in learning materials, especially reading texts presented in the textbooks used in the learning process in the classroom is very important for success of learning. The materials of ELT (English Language Teaching) books are supposed to provide sufficient quantity and range of words, vocabulary improvement, and strategies for self-learning. But, this study is focused only on the lexical units introduced in the reading texts. Two problems are questioned to figure out the lexical items of the reading materials presented in the ELT book: how many lexical units consider the most frequent words in English corpora and how many lexical units are presented in rehearsal or iteration. Descriptive quantitative methodology was used to research an e-book, Developing English Competencies 3, which the corpus became the object in this study. Observation and computational tool; RANGE and FREQUENCY, were applied as the instrument to make easier counting and analyzed by comparing to general frequency list. It was found that the book was clearly unbalanced about the amount and distribution throughout the three ranges. Then, the opportunities for repetitive practice were very poor. Many frequent words did not fit the English general scale of frequency.